THE EFFECT OF TIKTOK APPLICATION ON ENGLISH VOCABULARY MASTERY OF THE SECOND GRADE STUDENTS JUNIOR HIGH SCHOOL AT SMP ISLAM TAHFIDZ QUR'AN OF BIMA CITY - Uswatun Hasanah; Ahmad Zamzam; Husnul Lail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purposed of this study is to describe the significant influence of using the TikTok application on the vocabulary mastery of class II junior high school students at Tahfidz Qur'an Islamic Junior High School, Bima City. This type of research uses quasi-experimental research with a sample size of 40 class II junior high school students at Tahfidz Qur'an Islamic Junior High School, Bima City. The data collection technique used in this research is a test to determine mastery of vocabulary and documentation with data analysis techniques, namely validity test, reliability test, normality test, homogeneity test, and hypothesis test. Based on the data analysis that has been carried out, it can be concluded that the results of hypothesis testing calculations with the help of the SPSS 20.00 for Windows program using the Independent Sample T-Test test technique at a significance level of 5%, obtained a value of tcount ≥ ttable (5,845 ≥ 2.024), and the value sig ≤ 0.05 (0.001≤ 0.05). So Ho is rejected and Ha accepts. This shows that the hypothesis (Ha) which states that the use of the TikTok application influences the English vocabulary mastery of class II Islamic Tahfidz Qur'an Junior High School students in Bima City, is declared accepted.